Epidemiology and prognosis of burn injuries in China: a meta-analysis - Pengcheng Li; Qingqing Zhang; Dongjie Li (European Journal of Medical Research)
Abstract Background Burns are a significant cause of disability and death. Nonfatal burns have drastic impacts on survivors’ lives. This study examines the epidemiological characteristics and prognostic factors of burn injuries of hospitalized patients in China. Methods Literature search was conducted in online databases and study selection was based on precise eligibility criteria. Meta-analyses of proportions were performed to estimate the relative incidence rates of burn injuries between 1980 and 2022 by age, total body surface area (TBSA), cause, and season. Odds ratios (ORs) were pooled and metaregression analyses were performed to seek prognostic factors for mortality. Results 23 studies (465,433 patients; 33% females [95%CI 30, 35]) were included. Incidence rates were higher for age groups 0–4 and 30–45 years. Incidence was higher in summer (29% [95%CI 27, 30]) and lower in autumn (21% [95%CI 20, 22]). The incidences of mild (TBSA 0–10%), moderate (TBSA 10–30%), severe (TBSA 30–50%), and very severe (TBSA > 50%) burns were 52% [95%CI 45, 59] 27% [95% CI 23, 32], 9% [95%CI 6, 13], and 8% [95%CI 6, 10], respectively. Scald (50% [95%CI 43, 57]) and flame (27% [95%CI 19, 37]) were the main sources of burns. The mortality rate was 3% [95%CI 2, 3]. Age (OR 2.283 [95% CI 1.441, 3.125]), TBSA (2.266 [95% CI 1.708, 2.824), burn severity (OR 1.064 [95% CI 1.025, 1.103]), and inhalation injury (OR 6.670 [95% CI 3.032, 11.308]), and flame burns (metaregression coefficient: 0.128 [95% CI 0.029, 0.227]; p = 0.015) were associated with higher mortality. Conclusions In China, burn injuries remain a serious health concern. Young children (0–4 years of age) constitute a special risk group for safety measures. Burns due to flame are found to be more fatal than other causes.